Psychotic symptoms in young people warrant urgent referral. - Deakin, J; Lennox, B (2013)
There is a worse prognosis for psychosis and schizophrenia when onset is in childhood or adolescence. However, outcomes are improved with early detection and treatment. Psychotic symptoms can be associated with a variety of disorders including schizophrenia, schizoaffective disorder, drug-induced psychosis, personality disorder, epilepsy and autistic spectrum disorder. Positive symptoms include hallucinations and delusions. Negative symptoms include apathy, lack of drive, poverty of speech, social withdrawal and self-neglect. The DSM IV criteria for schizophrenia include two or more of the following: hallucinations, delusions, disorganised speech, grossly disorganised or catatonic behaviour and negative symptoms. Adults may raise concerns about social withdrawal, bizarre ideas, a change in behaviour or a decline in achievement. Most children and young people with psychotic symptoms will not go on to develop psychosis or schizophrenia. Direct enquiry may be needed to elicit suspected unusual beliefs or hallucinations. To distinguish unusual ideas from delusions the ideas should be tested for fixity. For example by asking: 'Are you sure? Could there be another explanation?' Mood and anxiety symptoms should be explored. The assessment should include a developmental history with particular attention to premorbid functioning. Failure to make expected progress whether personal, social or academic is significant. Better outcomes in terms of symptoms and social function are associated with a shorter duration of untreated psychosis. The detection of psychotic symptoms in primary care therefore warrants an urgent referral to secondary care mental health services for assessment and treatment.